2022
DOI: 10.3390/ijerph19010576
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Emotional Effects of Digitalised Work: The Case of Higher Education in the Sustainable Development

Abstract: This paper reports on the experiences of working with new digital tools along with the experience of new remote work. We explore the emotional experiences of working from home during the first three months of the COVID-19 pandemic and their implications. There were two groups of respondents participating in the study, those who had experience working remotely before the pandemic [digital natives] and those who started working remotely during the pandemic [digital immigrants]. The results show that emotional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Anyone may reproduce, distribute, translate and create derivative works of this article (for both commercial and non-commercial purposes), subject to full attribution to the original publication and authors. The full terms of this licence may be seen at http://creativecommons.org/licences/by/4.0/legalcode Knowledgerelated tensions post-pandemic period, when various hybrid work arrangements will be adapted, and remote work will possibly remain on a wider scale than before the pandemic (Staniec et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anyone may reproduce, distribute, translate and create derivative works of this article (for both commercial and non-commercial purposes), subject to full attribution to the original publication and authors. The full terms of this licence may be seen at http://creativecommons.org/licences/by/4.0/legalcode Knowledgerelated tensions post-pandemic period, when various hybrid work arrangements will be adapted, and remote work will possibly remain on a wider scale than before the pandemic (Staniec et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially the case in knowledge-intensive organizations, such as higher education institutions (HEIs), which have mostly transitioned to a remote work mode during the lockdown. Currently, work life is in preparation for the post-pandemic period, when various hybrid work arrangements will be adapted, and remote work will possibly remain on a wider scale than before the pandemic (Staniec et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These practices have generated harmful situations for workers, such as presenteeism, a perception of increased workload, and even physical and mental health problems in Colombian professionals [ 9 ]. In addition, Staniec et al [ 10 ] found that, during the first 3 months of the COVID-19 pandemic, the emotional experiences of working from home were similar between people with pre-pandemic remote work experience and people who had to migrate to the modality.…”
Section: Introductionmentioning
confidence: 99%
“…Colombian professionals [9]. In addition, Staniec et al [10] found that, during the first 3 months of the COVID-19 pandemic, the emotional experiences of working from home were similar between people with pre-pandemic remote work experience and people who had to migrate to the modality.…”
Section: Introductionmentioning
confidence: 99%